POPE FRANCIS ON DEMOCRACY - Míčka, Roman (Asian Horizons, 2020)
This article makes a brief introduction to the history of the development of the social teaching of the Church on democracy. Then it identifies and analyses fifteen relevant statements about democracy in the writings and speeches of Pope Francis between 2014 and 2020. Pope Francis through his writings and speeches reflects and further develops the concept of democracy in the social teaching of the Church. He uses positive terms about democracy as “inclusive and participatory democracy,” “strengthening of political and social democracy” and critical terms. For example, democracies according to him are “under the pressure” of “uniform systems of economic power,” it faces the danger of “subtle dictatorship,” “democracy atrophies,” it can become “democracy of words”; “nominal democracy,” extremism and populism can make “debilitating of the democratic system.” Besides, those statements are examined and put into context with current trends in politics and the theoretical study of democracy. Statements of Pope Francis give the impression that he is a relatively radical critic of the weaknesses of contemporary democracies and a supporter of its more radical forms.